Study of Heat Transfer Control with Magnetic Field Using Higher Order Finite Difference Scheme (Advances in Applied Mathematics and Mechanics, 2018)
The control of convective heat transfer from a heated circular cylinder immersedin an electrically conducting fluid is achieved using an externally imposedmagnetic field. A Higher Order Compact Scheme (HOCS) is used to solve the governingenergy equation in cylindrical polar coordinates. The HOCS gives fourth orderaccurate results for the temperature field. The behavior of local Nusselt number, meanNusselt number and temperature field due to variation in the aligned magnetic field isevaluated for the parameters 5≤$Re$≤40, 0≤$N$≤20 and 0.065≤$Pr$≤7. It is found thatthe convective heat transfer is suppressed by increasing the strength of the imposedmagnetic field until a critical value of $N$, the interaction parameter, beyond which theheat transfer increases with further increase in $N$. The results are found to be in goodagreement with recent experimental studies.